CrimeBites HQ / Nur Alya Tasneem Baharom - Baharom, Nur Alya Tasneem (2021)
In this business opportunity, I need to describe all information about my business. What I need to do is, to describe how I plan my business and how it started. Addition more, I must describe what product that I sells, my target, who is my customer and so on. This case study is important to identify business opportunities based on evaluation and selection. The method used to be obtain the needs and wants of customer are through personal interview and self-observation. I decided to study on is online. It is because during pandemic covid-19 people were preferred to online shopping than walk-in. Besides that, online shopping has a strong influence and buyers are consists of various age groups and communities. For example student, workers, housewife and others. This method are convenience and a pleasure for buyers because they can buy it anytime they want. There are two business opportunities that I have thought based on needs and wants of my target markets in online are skincare shop and cookies shop. SWOT Analysis is conducted in analyzing these business opportunities for me to open a business. I have choose cookies shop as my business as I have a moderate experience, knowledge and skill in cookies. The main reason why I choose to open cookies shop is because my high interest in operating it